2018
DOI: 10.1038/s41598-017-19058-3
|View full text |Cite
|
Sign up to set email alerts
|

Partially oxidized polyvinyl alcohol conduitfor peripheral nerve regeneration

Abstract: Surgical reconstruction of peripheral nerves injuries with wide substance-loss is still a challenge. Many studies focused on the development of artificial nerve conduits made of synthetic or biological materials but the ideal device has not yet been identified. Here, we manufactured a conduit for peripheral nerve regeneration using a novel biodegradable hydrogel we patented that is oxidized polyvinyl alcohol (OxPVA). Thus, its characteristics were compared with neat polyvinyl alcohol (PVA) and silk-fibroin (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 40 publications
(45 reference statements)
5
46
0
Order By: Relevance
“…Decellularized, homogenized and lyophilized sheets from articular cartilage, Wharton's Jelly and small intestine were cross-linked to PVA, obtaining bio-hybrid supports that sustained cell adhesion and proliferation [25][26][27]. In parallel, we proposed for the first time a standardized method to perform chemical oxidation of PVA by KMnO 4 in acid environment, in order to obtain scaffolds with improved swelling kinetics and protein adsorption/release ability with respect to neat PVA, as well as with tunable biodegradation properties which increase along with the degree of oxidation [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Decellularized, homogenized and lyophilized sheets from articular cartilage, Wharton's Jelly and small intestine were cross-linked to PVA, obtaining bio-hybrid supports that sustained cell adhesion and proliferation [25][26][27]. In parallel, we proposed for the first time a standardized method to perform chemical oxidation of PVA by KMnO 4 in acid environment, in order to obtain scaffolds with improved swelling kinetics and protein adsorption/release ability with respect to neat PVA, as well as with tunable biodegradation properties which increase along with the degree of oxidation [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…SF is a natural protein that is produced by Bombyx mori (silkworm; Xue et al, ). It is biocompatible and biodegradable (Stocco et al, ; Xue et al, ) and easily degraded by proteolytic enzymes. The SF conduit is a relatively new alternative to tissue engineering applications.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…Although it has been approved by the FDA , SF is still being researched for its clinic applications (Cao & Wang, ). In 2017, some studies have shown that a silk conduit applied to repair a gap of 5 mm (Stocco et al, ) and a larger gap of 30 mm (Xue et al, ) would improve sciatic nerve regeneration (Stocco et al, ; Xue et al, ). Wang et al, in 2018, also showed that a silk conduit by improving angiogenesis would promote the sciaticnerve regeneration across a 10‐mm‐long gap in rats (Wang & Sakiyama‐Elbert, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized PVA (OxPVA) along with axon regeneration exhibited the proper elasticity and manipulation. OxPVA promoted the myelination and axon density . In comparison with other biomaterials, PVA shows an excellent effects in biomedical application like to ECM.…”
Section: Introductionmentioning
confidence: 91%